2006
DOI: 10.1021/ac060643i
|View full text |Cite
|
Sign up to set email alerts
|

Fast Responsive Crystalline Colloidal Array Photonic Crystal Glucose Sensors

Abstract: We developed new photonic crystal polymerized crystalline colloidal array (PCCA) glucose sensing materials, which operate on the basis of formation of cross-links in the hydrogel. These materials are composed of hydrogels that embed an array of approximately 100-nm-diameter monodisperse polystyrene colloids that Bragg diffract light in the visible spectral region. The hydrogels change volume as the glucose concentration varies. This changes the lattice spacing, which changes the wavelength of the diffracted li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
230
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(236 citation statements)
references
References 33 publications
2
230
0
4
Order By: Relevance
“…Fits for the membrane permeability, k, yield consistent values for various values of C out . The response time of the silicone capsules to osmotic pressure differences is on the order of 10 3 s, comparable to that of colorimetric sensors based on polymerized crystalline colloidal arrays 11 . The response can potentially be improved by using elastic membranes with higher permeability.…”
Section: Article Nature Communications | Doi: 101038/ncomms4068mentioning
confidence: 66%
See 1 more Smart Citation
“…Fits for the membrane permeability, k, yield consistent values for various values of C out . The response time of the silicone capsules to osmotic pressure differences is on the order of 10 3 s, comparable to that of colorimetric sensors based on polymerized crystalline colloidal arrays 11 . The response can potentially be improved by using elastic membranes with higher permeability.…”
Section: Article Nature Communications | Doi: 101038/ncomms4068mentioning
confidence: 66%
“…Such dynamic control is especially useful for reflective colour displays, which have been fabricated by embedding colloidal particles in a polymer matrix whose swelling is controlled by an external electric field 6,7 . Dynamic control of diffraction has also be exploited to create colorimetric biosensors that change their structural colour upon specific binding of a biomolecule [8][9][10][11][12][13] . In all of these cases, the modulation of the photonic properties is controlled by changing the interparticle spacing, which requires fluid to flow out from the crystal; this transport is limited by diffusion, and thus rapid response requires small dimensions.…”
mentioning
confidence: 99%
“…Other signaling mechanisms such as electrochemical detection have also been demonstrated while few examples of optical sensors are known (25,30,(45)(46)(47)(48)(49). In particular, very few colorimetric sensors have been reported (25,45,50,51). We are interested in making hydrogel-based colorimetric sensors since hydrogels are transparent and can therefore be observed with a low optical background, allowing low concentration of labels to be visually detected.…”
Section: Introductionmentioning
confidence: 99%
“…15 Asher et al have reported the use of polymerized crystalline colloidal array (PCCA) of polystyrene as a novel sensing material for the detection of glucose, organophosphate pesticides and cancer marker with enzyme-based sensors. 16,17 As the PCCA hydrogel undergoes a volume change, the spacing between particles will change, resulting in the shift of reflectance wavelength following Bragg's law. [18][19][20] Since most OP compounds are hydrophobic and exhibit low solubility in water media, on-site detection is indeed difficult.…”
Section: Introductionmentioning
confidence: 99%